(untitled) (Asian Journal of Social Science Studies, 2019)
With the advent of the 21st century, China has entered the era of the Internet, and the tourism industry has continued to develop. The demand for domestic tourism and national leisure consciousness has been continuously improved. As the transformation of tourism forms has gradually shifted to leisure, experience and diversification, micro-tourism springs up. In 2011, micro-tourism was officially put on the agenda as an emerging form of tourism. After that, it became popular and developed rapidly. Large numbers of micro-tourism products dominated by 1-2 days of hot spring tour, ancient town tour, island tour, country tour, and suburb tour were launched online instantly. This paper first expounds the background, formation, development and characteristics of micro-tourism and then interprets the current development of micro-tourism from online survey data, finding that the development of micro-tourism market is good, but the related facilities and systems are comparatively lagging behind. Finally, the paper analyzes the micro-tourism resources and development conditions of Changsha city, finding that the foundation and market platform for developing micro-tourism in Changsha is sound. Given the actual development, the paper then puts forward development strategy for micro-tourism of Changsha City under the background of the Internet era, which may provide reference for other cities with similar conditions to develop micro-tourism.